Assessment Of Fluctuational And Critical Transformational Behaviour Of Ground Level Ozone - Awang, Norrimi Rosaida (2015)
Ground level ozone (O3) is a noxious air pollutant that imposed adverse effects to human health, crop yield and the environment. Hence, it is important to understand their fluctuation and transformation characteristics in Malaysia in order to design abatement and control strategies properly. Therefore, this study aimed at investigating the characteristics of O3 fluctuation and transformation from its precursors as well as to introduce the critical conversion point (CCP) of O3 formation in 18 monitoring stations across Malaysia from 1999 to 2010. The next hour O3 prediction models during daily, daytime, nighttime and critical conversion time were also developed using multiple linear regression (MLR) and principal components regression (PCR) to predict O3 concentrations in different groups of monitoring stations. Groups of monitoring stations were based on the Department of Environment, Malaysia in terms of classification and newly developed groups using ranking of means and cluster analysis. Although majority of the recorded data was below 100 ppb, total of 1,995 hour of exceedances have been recorded, with Shah Alam contributed 885 hour or 44.5%. O3 diurnal cycles suggested a uni-modal peak between 12 p.m. to 4 p.m., while minimum concentrations were consistently measured at 8 a.m.. Results of PCA showed the contributions to O3 variation by NO2, NO, temperature and UVB up to 80%, whereas the composite diurnal plots confirmed that variation is highly influenced by NO2 and NO concentrations. The CCP of O3 formation were identified to occur between 8 a.m. to 11 a.m.. The MLR model based on cluster group during daily exhibited optimal performance in terms of coefficient of determination, prediction accuracy, and index of agreement with values of 0.9351, 0.9671 and 0.9831,respectively.